ANALISIS PERAN P2MW DALAM MENINGKATKAN ORIENTASI KEWIRAUSAHAAN MAHASISWA - Sanju Efendi (FKIP Unswagati, 2026)
The Student Entrepreneurship Development Program (P2MW) is an activity to increase and develop entrepreneurial interests and talents within the university. This study aims to analyze the role of P2MW in strengthening the entrepreneurial interests of students in the Economics Education Study Program at Swadaya Gunung Jati University. This study uses a descriptive qualitative approach. The research subjects included students of Economics Education at Swadaya Gunung Jati University participating in P2MW, their supervisors, and the head of the study program. Data collection was conducted through interviews, observation, and documentation. The results show that P2MW acts as a means of experiential entrepreneurship learning that encourages the gradual formation of students' entrepreneurial interests. Business practice experience is the main source of learning that shapes students' entrepreneurial mindset and self-confidence. This study concludes that P2MW has a significant contribution in strengthening students' entrepreneurial interests, but requires optimization of ongoing mentoring and coaching so that students' businesses can develop more optimally. Keywords: Entrepreneurial Interest, P2MW, Entrepreneurship, Students.